Evidence of Moderation Maqashid Sharia : Financial Performance, Islamic Social Reporting and The Value of the Company: Bukti Moderasi Maqashid Syariah: Kinerja Keuangan, Pelaporan Sosial Islam Dan Nilai Perusahaan - Rismayanti, Dwi; Aisyah, Esy Nur (Universitas Muhammadiyah Sidoarjo, 2023)
Firm value influences investor perceptions to support the company's sustainability. The study aimed to analyze the effect of financial performance and islamic social reporting on firm value and the role of the maqashid sharia index in moderating financial performance and islamic social reporting on the company value of Islamic Commercial Banks in Indonesia. The research method used is quantitative. The sampling technique used purposive sampling with a sample of 6 Islamic Commercial Banks registered with the Financial Services Authority for 2017-2021. The data analysis method used in this study is SEM-PLS with the SmartPLS version 4.0.8.7 application. The results showed that the variables of financial performance and islamic social reporting had a significant effect on firm value. Then, the maqashid sharia index as a moderator variable cannot moderate the relationship between financial performance and islamic social reporting on firm value. Thus, the Maqashid sharia index is a moderator predictor because it can only independently influence the dependent variable.